What we know about poleroviruses : Advances in understanding the functions of polerovirus proteins - Delfosse, Veronica Cecilia; Barrios Baron, Maria Pilar; Distefano, Ana Julia (Wiley, 2024)
Poleroviruses are economically important plant viruses that infect cereal, vegetable, and fruit crops, and cause serious yield and quality losses worldwide. In this review we summarize the current knowledge of the function and regulation of polerovirus proteins and mention the methods employed by the different bodies of research that have produced these advances. Major biochemical and biological properties of these viral proteins are discussed in the order in which their open reading frames are organized in the genome.